MANAGEMENT OF MARKETING ACTIVITIES IN MANUFACTURING ENTERPRISES - Nosirov Javlonbek Jamoliddin o`gli (Journals Park Publishing, 2023)
The main purpose of this article is to assess how the new concept of marketing mix affects the delivery of value to customers and the benefit of the enterprise. The task of marketing management is to ensure the availability of goods and services when the customer is ready to buy. The enterprise needs accurate and relevant information about customers, competitors, the country and new socio-economic trends in the world. First of all, the analysis of the marketing management paradigm and the creation of value-based management are carried out. Then, the concept of marketing strategy and SWOT analysis is considered. Finally, the impact of information technology on marketing management is assessed.
Keywords: paradigm, values, strategy, SWOT, information technology.